Dual signal-enhanced immunochromatographic test strip based on Au@PtNPs: From sensitive detection of thiamethoxam to multiplex pesticide screening in vegetables - Zhengtao Li; Lingjun Geng; Jiashuai Sun; Jingcheng Huang; Rui Xu; Zhen Guo; Shouyi Dou; Liying Zhang; Fangling Du; Yemin Guo; Xia Sun; Nortoji A. Khujamshukurov (Food Chemistry, 2026)

Structure and antioxidant characteristics of diacylglycerol-based oleogels: A comparison with triacylglycerol systems - Hao Yue; Xiaoqing Zhang; Min Jia; Xiuxiu Wang; Baorui Li; Aizhen Zong; Fangling Du; Tongcheng Xu (Food Chemistry, 2026)

Crop rotations modulate chemical transformation of dissolved organic matter during mineral surface-bound Fe(II) oxidation in paddy soils - Cong Wu; Fangling Li; Taoyuan Ouyang; Wei Peng; Yanqi Xiao; Fu Liu; Qihong Zhu; Na Zhang; Hao-Jie Cui; Wenjuan Liao (Applied Geochemistry, 2026)

Cross-linked time-resolved fluorescence immunochromatographic strip for the detection of neonicotinoid pesticide residues: Competitive principle, rapid, reliable and environmentally friendly pretreatment - Peisen Li; Donghan Li; Haifang Wang; Jiashuai Sun; Lingjun Geng; Jingcheng Huang; Zhengtao Li; Nortoji A. Khujamshukurov; Yemin Guo; Xia Sun; Fangling Du (Food Research International, 2026)

A supersandwich fluorescent aptasensor leveraging the synergy of mini-nanotetrahedron, high-affinity split aptamer and rolling circle amplification for kanamycin analysis in milk - Xiaoyan Qi; Guoqiang Sun; Youjie Li; Pingyu Wang; Fangling Ning; Mengyuan Chu; Shuyang Xie (Food Chemistry, 2026)

A nanoengineered Au@Ag@PVP SERS solid-phase substrate empowered by machine learning for rapid and trace-level screening of pesticide residues in tea - Xifan Zhan; Xinying Wang; Md Mehedi Hassan; Fangling Jiang; Jiaying Xu; Yuan Zhang; Shanghua Li; Sha Zou; Hongfa Liu; Yi Xu; Quansheng Chen (Food Bioscience, 2026)

The transcription factor SlPLATZ22 negatively regulates salinity tolerance in tomato plants - Xin Li; Fei Ding; Niannian Zhou; Zheng Chen; Jiahui Huang; Fangling Jiang; Carl-Otto Ottosen; Ron Mittler; Rong Zhou; Zhen Wu (Journal of Plant Physiology, 2026)

Unveiling the synergistic regulation of Co-metabolic substrates and Fe(III) on tetrabromobisphenol A degradation by Geobacter sulfurreducens PCA - Zhenya Tang; Ruijiang Li; Ruijiao He; Jiwei Li; Zhenmin Dong; Hanzhang Wang; Fangling Fan; Qiliang Yang (Journal of Environmental Management, 2026)

Differentiation of positional isomers of branched-chain fatty acids using ion mobility-mass spectrometry based on host-guest chemistry - Naisheng Wu; Sisi He; Huiqi Ding; Fangling Wu; Yu Xiao; Li Ding; Chuan-Fan Ding (Food Chemistry, 2026)

Synergistic stabilization of cinnamaldehyde-loaded whey protein isolate microcapsules by tannic acid and chia seed polysaccharide: Insights into structure, function, interaction mechanism, and release characteristic - Liu Jiang; Kang Zheng; Yilin Li; Jianping Wang; Yemin Guo; Xia Sun; Fangling Du (Food Hydrocolloids, 2026)

Corrigendum to “Self-enhanced targeted nanomedicines based on iron starvation acclimation for tumor-specific therapy” [Chem. Eng. J. 495 (2024) 153371] - Zhenxin Guan; Jinghui Hu; Song Li; Yurong Liu; Xiaokang Zhang; Jinxiang Liu; Haoting Chen; Fangling Liao; Huiting Sun; Guige Hou; Weisheng Guo; Yafang Xiao; et al. (Chemical Engineering Journal, 2026)

Development and Application of a Method to Enhance Lipase Performance and Wastewater Treatment Capacity Using DES - Jiaxin Song; Chuanlong Yu; Fangling Wu; Li Yuan; Danna Fan; Yiheng Zhang; Yuping You; Guoqiang Wu; Zedong Zhang; Wenjun Wang (Sugar Tech, 2026)

Host size and parasite density impact on the efficacy and reproductive output of Pyemotes zhonghuajia, a biological control agent of potato tuber moth - Chenming Xiao; Xiong Zhao He; Xuelin Li; Di Fan; Long Zhang; Chengxu Wu; Maofa Yang; Jifeng Hu; Guy Smagghe; Jianfeng Liu; Fangling Xu (Experimental and Applied Acarology, 2026)

Population pharmacokinetic modeling and Monte Carlo simulation–based dosing optimization of trimethoprim–sulfamethoxazole in critically ill patients - Min Wang; Chen Li; Xiangxiang Fu; Fangling Wang; Xiaojun Zhou; Bingli Zhang; Wenya Xu; Liqiu Liang; Zhenlin Lei; Hengxing Qu; Ling Xie; Lili Zhong; et al. (European Journal of Clinical Pharmacology, 2026)

Development of a graphene oxide-SELEX derived aptamer and a lateral flow biosensor for on-site visual detection of isofenphos-methyl - Mingxuan Fang; Yinghui Wang; Yifei Qin; Lingjun Geng; Zhengtao Li; Jiashuai Sun; Fangling Du; Yemin Guo; Xia Sun; Ibrahim A. Darwish (Food Chemistry, 2026)

Solubility and bioavailability enhancement of baicalin by modified citrus pectin: preparation, in silico, in vitro and in vivo evaluation - Wenxin Ma; Fangling Du; Tongcheng Xu; Xiuxiu Wang; Baorui Li; Hao Yue; Min Jia; Aizhen Zong (Food Hydrocolloids, 2026)

D-allulose alleviates DSS-induced colitis via regulating gut microbiota and bile acid metabolism - Gaoqi Ye; Na Xi; Genying Li; Ziyuan Wang; Zhaofeng Li; Tongcheng Xu; Fangling Du; Guangpeng Dou; Yiman Zhang; Jie Liu (Food Research International, 2026)

Insight into emulsion gels stabilized by soy protein isolate–flavonoid complexes: based on structural, interfacial, and emulsifying properties of the protein - Baorui Li; Shaokun Dou; Qian Li; Hao Yue; Aizhen Zong; Fangling Du; Tongcheng Xu (Food Research International, 2025)

Research progress on molecularly imprinted polymers (MIPs)-based sensors for the detection of organophosphorus pesticides - Lingjun Geng; Haifang Wang; Zhengtao Li; Jingcheng Huang; Xia Sun; Yemin Guo; Fangling Du (Food Chemistry, 2025)

International law concerning the environmental protection in Arctic: what is left behind UNCLOS and the BBNJ Agreement? - Fangling Wu; Tiansheng Li (Frontiers in Marine Science, 2025)
The Arctic region, with its unique and fragile ecosystem, faces significant challenges in environmental protection due to climate change, increasing human activities, and geopolitical tensions. This paper examines the international legal framework governing Arctic environmental protection, focusing on the roles and limitations of the United Nations Convention on the Law of the Sea (UNCLOS) and the Agreement on the Conservation and Sustainable Use of Marine Biological Diversity of Areas Beyond National Jurisdiction (BBNJ Agreement). While UNCLOS provides a foundational legal framework for ocean governance, its applicability in addressing Arctic environmental concerns should be acknowledged, as should the complementary role of the BBNJ Agreement. However, the lack of provisions specific to Arctic environmental issues creates a gap between the effectiveness of international law and the urgent need for a comprehensive legal regime tailored to the Arctic context. Furthermore, the supplementary role of the BBNJ Agreement to UNCLOS remains limited. By highlighting key challenges in the implementation of international law, including disputes over Article 234 of UNCLOS, this study underscores the urgent need for a more robust and cohesive international legal approach to ensure the sustainable future of the Arctic environment, and concludes with appropriate recommendations.

Peroxisomal biogenesis factor 11 as a novel target to trigger lipid biosynthesis and salt stress resistance in oleaginous Tetradesmus obliquus - Yunzhuan Xue; Wei Wang; Xiajule Sheng; Zexu Zheng; Zihan Wang; Fangling Ding; Jinjin Li; Zhiwei Sun; Yu’ang Cai; Xianhua Wang; Jiao Xue (Bioresource Technology, 2025)

Effect of microphysical schemes on simulating severe convection induced by the northeast cold vortex using dual-polarization radar data - Fangling Yao; Xin Li; Zhengkun Qin; Gang Chen; Xiao Dong (Meteorology and Atmospheric Physics, 2025)

Molecular mechanisms underlying the effects of antibiotics on the growth and development of green tide algae Ulva prolifera - Fangling Bi; Qunjing Bao; Hongtao Liu; Jingyi Sun; Wei Dai; Aiqin Li; Jianheng Zhang; Peimin He (Marine Pollution Bulletin, 2024)

Self-enhanced targeted nanomedicines based on iron starvation acclimation for tumor-specific therapy - Zhenxin Guan; Jinghui Hu; Song Li; Yurong Liu; Xiaokang Zhang; Jinxiang Liu; Haoting Chen; Fangling Liao; Huiting Sun; Guige Hou; Weisheng Guo; Yafang Xiao; et al. (Chemical Engineering Journal, 2024)

Structures of multiple states of the nicotinamide nucleotide transhydrogenase from Escherichia coli - Jiao Li; Sangjin Hong; Xiuxiu Ma; Fangling Xu; Quan Li; Fan Wang; Kai Zhang; Robert B. Gennis; Jiapeng Zhu (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Structure and mechanism of the energy-coupled nicotinamide nucleotide transhydrogenase from E. Coli - Robert B. Gennis; Jiao Li; Sangin Hong; Xiuxiu Ma; Fangling Xu; Quan Li; Fan Wang; Kai Zhang; Jiapeng Zhu (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Model Test Study on Response of Weathered Rock Slope to Rainfall Infiltration under Different Conditions - Cong Li; Rongtang Zhang; Jiebing Zhu; Bo Lu; Xiaowei Wang; Fangling Xu; Xiaoke Shen; Jiesheng Liu; Weizhen Cai (Journal of Earth Science, 2024)

Overwintering and summer survival of Ulva prolifera in sediments: Indoor simulation of temperature impacts - Aiqin Li; Shuang Zhao; Jingyi Sun; Hongtao Liu; Yuqing Sun; Fangling Bi; Zhangyi Xia; Wei Dai; Wenhui He; Jianheng Zhang; Peimin He (Marine Pollution Bulletin, 2024)

Mechanisms of harmful effects of Microcystis aeruginosa on a brackish water organism Moina mongolica based on physiological and transcriptomic responses - Hongtao Liu; Hao Xing; Zhangyi Xia; Tingting Wu; Jinlin Liu; Aiqin Li; Fangling Bi; Yuqing Sun; Jianheng Zhang; Peimin He (Harmful Algae, 2024)

Responses of photosynthesis-related genes in Sargassum horneri to high temperature stress - Wei Dai; Xiaoran Wang; Minmin Zhuang; Jingyi Sun; Yifei Shen; Zhangyi Xia; Tingjian Wu; Ruitong Jiang; Aiqin Li; Fangling Bi; Jianheng Zhang; Peimin He (Marine Pollution Bulletin, 2024)

Progress in the treatment of copper(II)-containing wastewater and wastewater treatment systems based on combined technologies: A review - Qingyun Li; Yunfeng Wang; Zhuo Chang; Wael El Kolaly; Fangling Fan; Ming Li (Journal of Water Process Engineering, 2024)

Hypoxia-triggered tumor specific glutamine inhibition for reversing cisplatin resistance of chemotherapy - Jiaying Zhang; Jinghui Hu; Weiwei Zhu; Yurong Liu; Song Li; Haoting Chen; Fangling Liao; Qun Zhang; Xuan Sun; Xinting Li; Yafang Xiao; Jing Chen (Chemical Engineering Journal, 2024)

Changed cortical thickness and sulcal depth in pediatric acute lymphoblastic leukemia survivors treated with chemotherapy only - Fangling Li; Yimin Guo; Gaoqiang Xu; Ying Liu; Xiaoxi Chen; Tijiang Zhang (Brain Imaging and Behavior, 2023)

Effects of whole grain intake on glycemic traits: A systematic review and meta-analysis of randomized controlled trials - Shixiang Li; Aizhen Zong; Ran An; Haiou Wang; Lina Liu; Jie Liu; Xiaofei Guo; Zhixiang Xu; Jing Wang; Duo Li; Fangling Du; Tongcheng Xu (Critical Reviews in Food Science and Nutrition, 2023)

A cyclodextrin-based reagent for cis/trans-geometrical isomers separation by mobility measurements and chemical calculations - Fangling Wu; Xishi Wu; Zhe Li; Di Zhang; Chuan-Fan Ding (Food Chemistry, 2023)

Organic ligands activate the dark formation of hydroxyl radicals (HO•) in surface soil/sediment: Yields, mechanisms, and applications - Yufan Yuan; Fangling Guan; Chenglong Yu; Danping Li; Faying Lai; Huajun Huang; Jinbao He; Yanpeng Gao; Hansun Fang (Journal of Hazardous Materials, 2023)

Establishment and characterization of an immortalized human chondrocyte cell line - Jiashu Yang; Yuting Tang; Wensun Chen; Ming Zhang; Fangling Hong; Dawei Yang; Qianyi Bao; Ying Yang; Yucui Jin; Lingyun Li; Changyan Ma (Biotechnology Letters, 2020)

Comparison of Gefitinib Versus VMP in the Combination with Radiotherapy for Multiple Brain Metastases from Non-small Cell Lung Cancer - Feng Wang; Fangling Ning; Changmin Liu; Yanzhang Hao; LiMian Li; Zeshun Yu; Shaoshui Chen; Baosheng Li (Cell Biochemistry and Biophysics, 2015)

A novel cold-inducible gene from Pak-choi (Brassica campestris ssp. chinensis), BcWRKY46, enhances the cold, salt and dehydration stress tolerance in transgenic tobacco - Feng Wang; Xilin Hou; Jun Tang; Zhen Wang; Shuming Wang; Fangling Jiang; Ying Li (Molecular Biology Reports, 2012)

Components of the Arabidopsis CBF Cold-Response Pathway Are Conserved in Non-heading Chinese Cabbage - Fangling Jiang; Feng Wang; Zhen Wu; Ying Li; Gongjun Shi; Jingding Hu; Xilin Hou (Plant Molecular Biology Reporter, 2011)